The impact of blockchain on a South African top tier bank's operational efficiencies - Khaole, Thipe (My University, 2019)
Traditionally, banking transactions have been maintained within ledgers with different parties maintaining copies of their own ledgers, resulting in inevitable disputes. These disputes are minimised by utilising intermediaries, such as banks that are able to assist but at a cost, added on to overall business costs. BlockChain has become one of the most exponential and disruptive technologies of the last decade, and as a result, its adoption within financial services, specifically commercial banking, has grown in this period. The purpose of this study is to analyse the impact of BlockChain enabled solutions in their ability to enable operational efficiencies within a South African bank. This impact then assessed based on respondent groups that were surveyed separately and analysed in parallel. The last few years have seen the growth of distributed ledger technologies, least of all through multiple digital currencies and adoption for transacting in them across service providers. With the advent of technologies like BlockChain that seek to minimise the involvement of third parties and intermediaries such as banks, how banks embrace the technology to remain relevant and necessary is crucial to the commercial banking sector. It is proposed that there are benefits that can be achieved from resultant operational efficiencies as a result of embracing the technology within the South African commercial banking sector. This is primarily through the possibility of enabled efficiencies through banking use case adoption, including but not limited to use cases such as regulatory reporting process automation and asset loan provisioning through simplified KYC (know your customer) processes. Keywords: BlockChain; operational efficiency; exponential technologies; smart contracts; streamlined processes; digital currency; distributed ledger technology; commercial banking
MBA
Keywords: Blockchains (Databases) Banks and banking -- South Africa. Technological innovations.